1999
DOI: 10.1021/jm981074c
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of (2,2‘:6‘,2‘ ‘-Terpyridine)platinum(II) Complexes to Leishmania donovani, Trypanosoma cruzi, and Trypanosoma brucei

Abstract: A range of (2,2':6',2''-terpyridine)platinum(II) complexes are shown to possess antiprotozoal activity in vitro against Leishmania donovani, Trypanosoma cruzi, and Trypanosoma brucei,the causative organisms of tropical diseases leishmaniasis and trypanosomiasis. The best compounds caused 100% and 78% inhibition of growth of the intracellular amastigote forms of L. donovani and T. cruzi, respectively, at a concentration of 1 microM and 100% inhibition of growth of the bloodstream trypomastigote forms of T. bruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
100
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 17 publications
0
100
0
2
Order By: Relevance
“…This strategy has been performed to enhance the potency of ketoconazole, clotrimazole, benznidazole, risedronate, and quinolones (34)(35)(36)(37)(38)(39). Alternatively, metal complexes which are composed of ligands with unique chemical properties (redox and electrochemical behavior based on ligand reductions) exhibit anti-T. cruzi properties, possibly due to parasite membrane accumulation, in addition to effects on DNA and enzymes (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been performed to enhance the potency of ketoconazole, clotrimazole, benznidazole, risedronate, and quinolones (34)(35)(36)(37)(38)(39). Alternatively, metal complexes which are composed of ligands with unique chemical properties (redox and electrochemical behavior based on ligand reductions) exhibit anti-T. cruzi properties, possibly due to parasite membrane accumulation, in addition to effects on DNA and enzymes (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proposed strategies incorporating the use of cisplatin in combination with other drugs such as perillyl alcohol, other platinum(II) compounds, and AG1478 to accelerate cisplatin-induced apoptosis in several glioma cell lines (24)(25)(26)(27)(28). Furthermore, combination of CsA with other anticancer drugs has been shown to enhance chemotherapeutic efficacy in leukemia and gastric carcinoma cells (29,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation in clinical use of cisplatin is acquisition of resistance by initially responsive tumors (23). Combinational use of cisplatin with other drugs, such as perillyl alcohol, other platinum(II) compounds, or AG1478, accelerates cisplatininduced apoptosis in several glioma cell lines (24)(25)(26)(27)(28). Moreover, recent studies have indicated that CsA enhances docetaxel-induced apoptosis in human gastric carcinoma cells (29).…”
Section: Introductionmentioning
confidence: 99%
“…Novel approaches at the design of antileishmanial agents include the specific dihydrofolate reductase inhibitor 78 (IC 50 ¼ 6.0 mM) (Fig. 21) [175] and (terpyridine)-platinum(II) complexes such as 79, which are effective against L. donovani (100% inhibition at 1 mM), T. cruzi (65% inhibition at 1 mM), and T. b. brucei (100% inhibition at 30 nM) [176]. The triphenyltin complex 80 also has antileishmanial activity, and depletes amastigotes in cultured hamster macrophages to undetectable levels at a concentration of 10 mg/L [177].…”
Section: Potential New Therapies For Leishmaniasismentioning
confidence: 99%